C-Reactive Protein Level Is an Indicator of the Aggressiveness of Advanced Pancreatic Cancer. Issue 1 (January 2016) - Mitsunaga, Shuichi; Ikeda, Masafumi; Shimizu, Satoshi; Ohno, Izumi; Takahashi, Hideaki; Okuyama, Hiroyuki; Ueno, Hideki; Morizane, Chigusa; Kondo, Shunsuke; Sakamoto, Yasunari; Okusaka, Takuji; Ochiai, Atsushi
Abstract : Objectives: This study investigated the ability of serum levels of C-reactive protein (CRP) to stratify the aggressiveness of advanced pancreatic cancer (PCa), including poor outcomes, systemic weakness, and extent of the disease in patients receiving first-line chemotherapy. Methods: The prognostic CRP classification was constructed in the retrospective cohort, consisting of advanced PCa patients with first-line gemcitabine monotherapy (GEM). Stratification using the prognostic CRP classification was validated for relationships with the aggressiveness of advanced PCa in the prospective cohort, consisting of treatment-naive patients without obvious infections who received first-line GEM or GEM-based regimens. Results: C-reactive protein low (<0.5 mg/dL), intermediate (≥0.5 and <2.0 mg/dL), and high (≥2.0 mg/dL) related good, moderate, and poor survival, respectively, and were independent predictors of survival in multivariate analyses among the 280 patients in the retrospective cohort and the 141 patients in the prospective cohort. Low Karnofsky Performance Status, hypoalbuminemia, anemia, and large tumor burden were more common in the high CRP group than in the low CRP group. The intermediate CRP group showed a larger burden of tumor than the low CRP group. Conclusions: C-reactive protein stratified the outcomes, systemic weakness, and tumor burden. C-reactive protein is an indicator of the aggressiveness of advanced PCa.